DNA replication licensing factors and aurora kinases are linked to aneuploidy and clinical outcome in epithelial ovarian carcinoma. - Kulkarni, A; Loddo, M; Leo, E; Rashid, M; Eward, K; Fanshawe, T; Butcher, J; Frost, A; Ledermann, J; Williams, G; Stoeber, K (2007)
PURPOSE: DNA replication licensing factors and Aurora kinases play critical roles in maintaining genomic integrity. We used multiparameter analyses of these cell cycle regulatory proteins to investigate their role in the progression of epithelial ovarian carcinoma (EOC). EXPERIMENTAL DESIGN: In a cohort of 143 patients, we linked the protein expression profiles of the proliferation marker Ki67, the replication licensing factors Mcm2 and geminin, and the Aurora A and B kinases to tumor DNA ploidy status and clinical outcome. RESULTS: Ki67, Mcm2, geminin, and Aurora A and B are significantly associated with tumor grade and ploidy status (P < 0.0001). Aurora A and its substrate H3S10ph are also significantly associated with Federation of International Obstetricians and Gynecologists tumor stage (P = 0.006 and P = 0.002, respectively). Aurora A and tumor ploidy status are predictive of disease-free survival in this cohort [hazard ratio (HR), 1.29; 95% confidence intervals (95% CI), 1.06-1.58, P = 0.01 and HR, 1.80 (1.05-3.08), P = 0.03, respectively], with Aurora A of particular prognostic importance in early stage disease [HR, 1.72 (1.19-2.48), P = 0.004 for disease-free survival and HR, 1.81 (1.14-2.87), P = 0.01 for overall survival]. CONCLUSIONS: Our data show that Ki67, Mcm2, geminin and Aurora A and B can be used as an adjunct to conventional prognostic indicators and as an aid to develop a tumor progression model for EOC. Dysregulation of Aurora A seems to be an early event in EOC with a key role in tumor progression. In view of present drug development programs for specific Aurora kinase inhibitors, our findings have important implications for the use of Aurora A as a biomarker and as a potential therapeutic target.